Optimisation of foliar application of zinc and boron in small cardamom (Elettaria cardamomum Maton) - Oommen, Manoj; Sundari, A.; Thomas, J. (Journal of Plantation Crops, 2011)
A field experiment was conducted at Indian Cardamom Research Institute, Spices Board, Myladumpara, Idukki district, Kerala during 2006-09 to study the response of foliar application of zinc and boron on growth, yield and its content in index leaves in small cardamom. The experiment was laid out in randomized block design with twelve treatments replicated thrice. The treatments were various levels of zinc (0.1, 0.25, 0.5, 0.75 and 0.9 %) as zinc sulphate and boron (0.2, 0.4, 0.6, 0.8, 1.0 and 1.2 %) as borax with a control. The zinc content in the leaves of zinc treated plants ranged from 53.79 mg kg-1 to 116.67 mg kg-1. The boron content in leaves of the boron treated plants ranged from 20.62 mg kg-1 to 34.37 mg kg-1. The DTPA extractable zinc in soil was 0.756 to 0.917 mg kg-1 in zinc treatments and 0.93 mg kg-1 in control plot. Hot water extractable boron in soil ranged between 0.90 mg kg-1 to 2.2 mg kg-1 in boron treatments and 0.850 mg kg-1 in control plot. Application of boron at 0.6 and 0.8 % significantly improved the yield of cardamom compared to control. A significant quadratic relationship was established between yield and various levels of zinc and the quadratic curve gives the zinc optimum dose as 0.38 %. The yield attributing characters like number of panicles per clump and number of racemes per panicle were positively influenced by the foliar application of zinc and boron.